EFFECT OF PARIS SAPONIN ON ANTITUMOR AND IMMUNE FUNCTION IN U14 TUMOR-BEARING MICE - GuangLie, Chen; WeiShi, Gao; GaiLing, Hou; JianPing, Cao (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
We evaluated the effect of Paris saponin on inhibition of cervical cancer in mice and on immune regulation in tumor-bearing mice. MTT assay was used to examine the effect of Paris saponin on U14 cell proliferatiosn in vitro; the ascites tumor model of U14 cervical cancer was established to observe the effect of Paris saponin on inhibition of the tumor and on survival time of mice; and serum IL-4 and IFN-γ levels in tumor-bearing mice were detected. The Paris saponin showed significant inhibitory effect on growth of cervical cancer U14 cells both in vitro and in vivo, prolonged the survival time of mice, increased the serum IFN-γ level of tumor-bearing mice, and reduced the serum IL-4 level. The Paris saponin can inhibit U14 cell growth and prolong survival time of mice; it is speculated that the Paris saponin may express its anti-tumor activity by improving the body's immune system. We evaluated the effect of Paris saponin on inhibition of cervical cancer in mice and on immune regulation in tumor-bearing mice. MTT assay was used to examine the effect of Paris saponin on U14 cell proliferatiosn in vitro; the ascites tumor model of U14 cervical cancer was established to observe the effect of Paris saponin on inhibition of the tumor and on survival time of mice; and serum IL-4 and IFN-γ levels in tumor-bearing mice were detected. The Paris saponin showed significant inhibitory effect on growth of cervical cancer U14 cells both in vitro and in vivo, prolonged the survival time of mice, increased the serum IFN-γ level of tumor-bearing mice, and reduced the serum IL-4 level. The Paris saponin can inhibit U14 cell growth and prolong survival time of mice; it is speculated that the Paris saponin may express its anti-tumor activity by improving the body's immune system.